Child’s Play as a Factor of Education of Moral Values in the Childhood - Jasiūnaitė, Placida (Jaunųjų mokslininkų darbai, 2024)
This article actualises the importance of education of moral values nurturing a full-fledged personality. Acknowledging the meaning and particularity of education of moral values in ontogenesis, the particular importance of primary education of moral values in the childhood is pointed out. Play stands out as one of the factors that determines the education of moral values processes in current world. On the basis of the scientific sources and data of researches, play is defined as the main child’s activity. Having discussed the effective use of child’s play in education of moral values (in this article from the holistic point of view), the varied influence of play on child’s education of moral values is revealed. Evaluating this effect from the point of view of child’s moral self-development, it is stated that through naturally occurring situations during play, a child is exposed to real possibilities to express moral values that help her//him to better adjust to their peers, to involve into group’s life and to achieve a favourable status. In terms of child’s individuality development, a child is able to acquire new moral abilities, skills, individual experience, norms and regulations, to experience joy and pleasures. Generalising, play may lay valuable foundation for the development of child’s moral and individual personality, which allows for considering play as a significant factor of education of moral values in the childhood.